2009
DOI: 10.1186/1472-6963-9-237
|View full text |Cite
|
Sign up to set email alerts
|

Comparing methods for identifying patients with heart failure using electronic data sources

Abstract: BackgroundAccurately indentifying heart failure (HF) patients from administrative claims data is useful for both research and quality of care efforts. Yet, there are few comparisons of the various claims data criteria (also known as claims signatures) for identifying HF patients. We compared various HF claim signatures to assess their relative accuracy.MethodsIn this retrospective study, we identified 4174 patients who received care from a large health system in southeast Michigan and who had ≥1 HF encounter b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 10 publications
0
34
0
1
Order By: Relevance
“…Cardiac disease registries were used in two studies [53], [54], while a specific set of diagnostic criteria were incorporated in the reference standards of the seven remaining studies [17], [34], [42], [44], [45], [55], [56].…”
Section: Resultsmentioning
confidence: 99%
“…Cardiac disease registries were used in two studies [53], [54], while a specific set of diagnostic criteria were incorporated in the reference standards of the seven remaining studies [17], [34], [42], [44], [45], [55], [56].…”
Section: Resultsmentioning
confidence: 99%
“…Hospitalization for HF was the first inpatient admission with a primary discharge diagnosis of HF during the period of observation. A primary hospital discharge diagnosis of HF has been shown by our group and others to be a highly specific claim signature for HF (specificity 95–100%)(16, 17). Secondary endpoints included all-cause hospitalization and all-cause mortality.…”
Section: Methodsmentioning
confidence: 87%
“…Finally, the information used in this study was primarily sourced from administrative and claims data. Although these sources have some potential for misclassification, we have previously shown that hospital discharge diagnoses for HF are highly specific (16) and that pharmacy claims produce consistently predictive measures of drug exposure (35). …”
Section: Discussionmentioning
confidence: 99%
“…Prior reports of the use of administrative data to identify various patient populations have shown sensitivities of 67% (urinary tract infections), 36-69% (heart failure), 76% (acute myocardial infarction), 83% (diabetes mellitus), 65% (hypertension), and 29% (PAD). [20][21][22] Hebert et al 9 applied a similar Medicare databased approach to identify diabetic patients using different algorithms, and reported sensitivity values ranging from 5% to 79%. The sensitivity of our algorithms ranged from 29% to 92%.…”
Section: Discussionmentioning
confidence: 99%